The Evaluation of Galectin-3 Levels in Non-dipper Hypertensive Patients - Akcay, Salaheddin; Cakin, Ozlem; Ilhan, Nevin; Kalayci, Hatice; Kobat, Mehmet Ali; Gulger, Mehtap; Bilge, Ali Riza (Elsevier Science Inc, 2013)
[Abstract Not Available]
29th Turkish Cardiology Congress of the Turkish-Society-of-Cardiology (TSC) with International Participation -- OCT 26-29, 2013 -- Antalya, TURKEY